Molecular simulation studies on the water/methane two-phase flow in a cylindrical silica nanopore: Formation mechanisms of water lock and implications for gas hydrate exploitation. (1st February 2023) - Zheng, Chao; Guo, Guang-Jun; Qin, Xuwen; Dong, Yanhui; Lu, Cheng; Peng, Bo; Tang, Wei; Bian, Hang
Graphical abstract: Highlights: Nano-manometer is newly proposed to measure the local pressure accurately in MD. Water lock suddenly stops the methane flow in a cylindrical silica nanopore. Features of water lock are fully studied and its morphology model is established. Water lock strikes the balance between water surface tension and pore wall adsorption. Abstract: The water/gas two-phase flow is a frequently encountered question in the percolation field, and is especially important for the exploitation of natural gas hydrates because their decomposition products are exactly liquid water and natural gas. We studied the water/methane two-phase flow in a hydrophilic cylindrical nanopore by performing molecular simulations, and obtained high-quality nanoflows under different water saturation ( S w ) thanks to the newly established nano-manometer method to control pressure difference accurately. With increasing S w, the methane flow decreases almost linearly until a sudden stop when S w  ≥ 0.52. The formation of the water lock accounting for this phenomenon is observed clearly, and the larger S w, the earlier formation of the water lock as well as the longer water lock. Based on careful data analysis, a water lock model and its formation mechanism are newly proposed with two pieces of strong evidence — the continuous reduction of the surface area of the water/gas interface when the water lock forms and the existence of maximum thickness of water film for different S w . Thus, the competition between the surface tension of the water/gas interface and the adsorption of the water/wall interface controls the development of the water lock. These findings are very helpful for understanding the two-phase percolation and optimizing the gas production and water removal schemes during hydrate exploitation. In addition, the nano-manometer can be widely used in other nanoflow simulations for measuring the local pressure accurately.